2017
DOI: 10.1038/s41598-017-00036-8
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of palmitoylated cysteines are essential for aggregation of cysteine-string protein mutants that cause neuronal ceroid lipofuscinosis

Abstract: Autosomal-dominant adult-onset neuronal ceroid lipofuscinosis (ANCL) is caused by mutation of the DNAJC5 gene encoding cysteine string protein alpha (CSPα). The disease-causing mutations, which result in substitution of leucine-115 with an arginine (L115R) or deletion of the neighbouring leucine-116 (∆L116) in the cysteine-string domain cause CSPα to form high molecular weight SDS-resistant aggregates, which are also present in post-mortem brain tissue from patients. Formation and stability of these mutant agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(91 citation statements)
references
References 18 publications
(51 reference statements)
15
76
0
Order By: Relevance
“…Potential templates with lower, but still significant homology (85–98% confidence) were identified in bacterial insecticidal toxins from Bacillus thuringiensis and Alcaligensis faecalis ( Kelker et al. 2014 ; Yalpani et al. 2017 ) and in the fungal sphingomyelin-binding/toxic proteins nakanori ( Makino et al.…”
Section: Resultsmentioning
confidence: 99%
“…Potential templates with lower, but still significant homology (85–98% confidence) were identified in bacterial insecticidal toxins from Bacillus thuringiensis and Alcaligensis faecalis ( Kelker et al. 2014 ; Yalpani et al. 2017 ) and in the fungal sphingomyelin-binding/toxic proteins nakanori ( Makino et al.…”
Section: Resultsmentioning
confidence: 99%
“…For example, both Cys and Ser [47], but not Gln, are known targets for post-translational protein palmitoylation, which anchors proteins to cellular membranes [48]. The palmitoylation of Cys residues in another protein, cysteine string protein α, is essential for protein aggregation and is associated with the neurodegenerative disease adult-onset neuronal ceroid lipofuscinosis [49]. Therefore, post-translational modification of polySer and polyCys, but not polyGln, may lead to protein interactions that drive protein aggregation in ways that are distinct from polyGln.…”
Section: Polycys and Polyser: Weakly Toxic Ran Productsmentioning
confidence: 99%
“…It is present in archaea and bacteria, mostly as monomeric proteins with two CDGSH domains [14, 31]. It has been suggested that the gene duplication that resulted in the eventual formation of mNT and NAF-1 in humans occurred around the time when vertebrates began to appear on Earth [31].…”
Section: Prefacementioning
confidence: 99%